Climate variability, women empowerment and intra-gender welfare allocation : effects on child nutrition and school absenteeism in Ethiopia - Abidoye, Babatunde O. (University of Pretoria, 2020)
Thesis (PhD (Agricultural Economics))--University of Pretoria, 2020.